Negative feedback regulation of vasocontraction by potassium channels in 10- to 15-day-old rats: dominating role of Kv7 channels - Shvetsova, Anastasia A.; Schubert, Rudolf (Acta physiologica, 2019)
Aim Potassium channels are key regulators of smooth muscle membrane potential and arterial tone. However, the roles of potassium channels in vascular tone regulation in the systemic circulation during early postnatal development are poorly understood. Therefore, this study tested the hypothesis that the negative feedback regulation of vasocontraction by potassium channels changes during maturation. Methods Experiments were performed on endothelium-denuded saphenous arteries from 10- to 15-day-old and 2- to 3-month-old male rats. Isometric force and membrane potential were recorded using wire myography and the sharp microelectrode technique respectively; mRNA and protein contents were determined by qPCR and Western blotting. Results The effects of Kv1, Kir and Kv7 channel blockers (DPO-1, BaCl2, XE991) on methoxamine-induced contraction were larger in arteries of 10- to 15-day-old compared to 2- to 3-month-old animals. In contrast, the BKCa channel blocker iberiotoxin had a stronger influence in 2- to 3- month-old rats. The effects of KATP and Kv2 channel blockers (glibenclamide, stromatoxin) were not pronounced at both ages. The larger influence of Kv7 and Kir channel blockade on arterial contraction in 10- to 15-day-old rats was associated with more prominent smooth muscle depolarization. The developmental alterations in potassium channel functioning were generally consistent with their mRNA and protein expression levels in arterial smooth muscle. Conclusion The negative feedback regulation of vasocontraction by potassium channels varies during maturation depending on the channel type. A dominating contribution of Kv7 channels to the regulation of basal tone and agonist-induced contraction was observed in arteries of 10- to 15-day-old animals.
Gesehen am 10.04.2019
Im Titel ist "v" in "Kv7" tiefgestellt
First published: 23 August 2018